Mental Health Day Hospitals and Lockdown Due to COVID-19 in Spain - Sánchez-Guarnido, Antonio José; Lucena, Valentina; Torrent, Aurora; Bosa, Laura; Martinez-López, Virginia; Cuartiles-Berenguer, Ana; Batalla, Iolanda (Frontiers in Psychology, 2022)
The COVID-19 pandemic has forced changes in patient care in mental health day hospitals (MHDHs). Objectives: To study the interventions performed in MHDHs during the pandemic in comparison with those performed in other facilities and to analyze the effectiveness of MHDHs in reducing new hospital admissions. Method: A retrospective multicenter cohort study comparing a group of 161 patients who received interventions in MHDHs during the lockdown period in Spain with another group of 109 patients who were treated at other facilities during lockdown. Results: MHDHs reduced their face-to-face interventions during lockdown just as much as other facilities but implemented telematic intervention methods to a greater extent. Patients attached to MHDHs during lockdown were admitted significantly less and presented fewer urgent consultations in the following six months. Conclusions: The use of telepsychiatry made it feasible to adapt MHDHs to periods of lockdown, being useful to improve the continuity of care during the pandemic and maintaining its effectiveness later when observing a reduction in hospital admissions.Men